Becoming a garments worker: The mobilization of women into the garments factories of Bangladesh - Nazli Kibria (United Nations Research Institute for Social Development (UNRISD), 1998)
Since the early 1980s an export-oriented garments industry has mushroomed in Bangladesh, with women workers constituting a significant proportion of its wage labour force. In explaining the reasons for the feminized wage labour force, considerable attention has been paid to the motivations of employers: the lower cost of young women workers, and their assumed "docility" and "nimbleness" in comparison to men. However, as Nazli Kibria argues, a fuller understanding of the movement of women into the garments factories of Bangladesh also requires the consideration of the "push" factors that underpin it. Conventional understandings of women's entry into wage employment in Bangladesh have emphasized the role played by extreme poverty and the related dynamic of male unemployment and desertion factors that are also explored in the present paper. But based on interviews with women factory workers in Dhaka, the author is able to suggest a more diverse set of factors underpinning their movement into the garments sector, which in a significant number of cases also entails individual rural-urban migration. Among the factors highlighted are family conflicts, marriage breakdowns, problems of sexual harrassment, the pressures from rising dowry demands and uncertain marriage prospects. Rather than being uniformly a response to dire poverty, the paper argues that in some instances garments work provides the means for enhancing personal and/or household economic prospects, while in other cases it provides a measure of economic and social independence for the women concerned. Another point emerging from the paper is that the meanings that are attached to any kind of work are context-specific and thus highly variable: notwithstanding the exploitative nature of work in garments factories, the value that women workers in this particular context attach to garments work needs to be seen in the light of other livelihood options that are open to them, such as domestic service and arduous forms of agricultural wage work.
Keywords: 330